Local labour market size and qualification mismatch - Francesco Berlingieri (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates the effect of the size of the local labour market on skill mismatch. Using survey data for Germany, we find that male workers in large cities are both less likely to be overqualified for their job and to work in a different field than the one they are trained for. Different empirical strategies are employed to account for the potential sorting of talented workers into more urbanized areas. Results on individuals never moving from the place of childhood and fixed-effects estimates obtaining identification through regional migrants suggest that sorting does not fully explain the existing differences in qualification mismatch across areas. This provides evidence of the existence of agglomeration economies through better matches. However, better job matching in larger cities seems to explain only a small part of the urban wage premium.
Keywords: R23; J24; J31; 330